(untitled) (African Human Mobility Review, 2023)
Statelessness constricts development opportunities, human capital and potentials of affected communities and persons over successive generations. The marginalisation of stateless persons, deprivation of their basic rights, legal recognition and access to essential services further induce their vulnerability and the risk of intergenerational statelessness. However, the nexus between statelessness and development remains poorly investigated amid the lack of coherent measures to address it. Hence, the need to understand the increased deprivations by statelessness and its conditions of vulnerability, suspicion, and exclusion, and the mismatch in the implementation of multilateral development programmes and national policies against statelessness. The paper maintains that neglect of stateless persons and communities by development actors and processes often lags them in global, regional, or national development. Although not explicitly encapsulated to address statelessness, the Sustainable Development Goals (SDGs) unlock significant opportunities, with relevance and applicability of several goals in this regard. Therefore, incorporating statelessness into the post-2030 development agenda is critical for addressing its challenges, and improving human security and conditions of stateless persons.